2021
DOI: 10.4197/islec.34-1.1
|View full text |Cite
|
Sign up to set email alerts
|

How Governance Practices Influence Mandatory Zakāh Payment in Saudi Arabia

Abstract: The purpose of this study is to investigate the influence of governance practices of the formal zakāh authority in Saudi Arabia, the GAZT (General Authority of Zakat and Tax), on zakāh payment compliance. It employs a quantitative approach using a questionnaire survey of actual zakāh payers in Saudi Arabia. The analysis of one hundred and twenty-five usable questionnaires collected through random sampling from al-Madinah region was done using the PLS (Partial Least Squares) - SEM (Structural Equation Models) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…In another country like Thailand, the responsibility of collection and distribution of zakat at the community, provincial, regional and national levels with integrity, transparency and good governance was needed in Thai's Islamic Social Financial Institutions (Boonyamanond and Chaiwat, 2020). In line with that, Saudi Arabia's case demonstrated that a relationship between the perceived governance of the zakat authority and zakat payment compliance was also mediated by trust (Sawmar and Mohammed, 2021). In Malaysia, waqf governance has been implemented by awqaf institutions but still needs improvement (Awaludin et al, 2018).…”
Section: Analysis Of Content and Future Research Directionsmentioning
confidence: 88%
“…In another country like Thailand, the responsibility of collection and distribution of zakat at the community, provincial, regional and national levels with integrity, transparency and good governance was needed in Thai's Islamic Social Financial Institutions (Boonyamanond and Chaiwat, 2020). In line with that, Saudi Arabia's case demonstrated that a relationship between the perceived governance of the zakat authority and zakat payment compliance was also mediated by trust (Sawmar and Mohammed, 2021). In Malaysia, waqf governance has been implemented by awqaf institutions but still needs improvement (Awaludin et al, 2018).…”
Section: Analysis Of Content and Future Research Directionsmentioning
confidence: 88%
“…The assessment of procedural justice is more strongly associated with attitudes toward political institutions and the political system as a whole than toward the procedures and the decisions the authorities make. In our opinion, this happens because the evaluation of political procedures and decisions depends on two factors: an assessment of the justice and positivity of the result, examples of the latter including the perceived effectiveness of the program or the bonuses that the citizen received from its implementation (e.g., Levi & Sacks, 2009; Sawmar & Mohammed, 2021; Van der Toorn et al., 2011; Zhong, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Third, we coded the type of situation: real versus hypothetical (Research Question 3). In a real situation, the respondents were asked about an experience of a real interaction with bodies and individuals such as government authorities and agencies (e.g., Azmi et al., 2016; Sawmar & Mohammed, 2021). In a hypothetical situation, the description of a fictitious event was formulated for and presented to the respondents.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tax and zakat are two distinct concepts, but both involve the payment of money to support the government and society. Muslim communities in Indonesia have an obligation to pay zakat, and also have an obligation to pay taxes (Panji Lestari et al, 2022;Saptono et al, 2023;Sawmar & Mohammed, 2021). Both of these are obligations that must be fulfilled by individual Muslims as citizens in Indonesia (Thamrin et al, 2023).…”
Section: Introductionmentioning
confidence: 99%